2022
DOI: 10.1186/s12891-022-05567-4
|View full text |Cite
|
Sign up to set email alerts
|

High levels of TDO2 in relation to pro-inflammatory cytokines in synovium and synovial fluid of patients with osteoarthritis

Abstract: Background Tryptophan 2,3-dioxygenase (TDO2) is the primary enzyme that catabolizes tryptophan to kynurenine. Numerous studies have suggested that TDO2 is involved in inflammation-related diseases. However, its role in osteoarthritis (OA) has not yet been investigated. The aim of the present study was to explore the levels of TDO2 in the synovium and synovial fluid (SF) of patients with OA and its correlation with clinical manifestations and levels of pro-inflammatory cytokines.  … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Studies have shown that the level of TDO2 in patients with OA was remarkably higher than these without arthritis. Further analysis found that the level of TDO2 in knee joint synovial membrane and synovial fluid of OA patients was positively correlated with clinical manifestations, KL grade and proinflammatory cytokine levels [ 22 ]. Recently, the expression of TDO2 has been reported to be highly upregulated in joint tissues of rheumatoid arthritis patients and rats with help-induced arthritis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the level of TDO2 in patients with OA was remarkably higher than these without arthritis. Further analysis found that the level of TDO2 in knee joint synovial membrane and synovial fluid of OA patients was positively correlated with clinical manifestations, KL grade and proinflammatory cytokine levels [ 22 ]. Recently, the expression of TDO2 has been reported to be highly upregulated in joint tissues of rheumatoid arthritis patients and rats with help-induced arthritis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In tryptophan metabolism, a variety of enzymes such as indoleamine 2,3‐dioxygenase 1 (IDO1), indoleamine 2,3‐dioxygenase 2 (IDO2) and tryptophan‐2,3‐dioxygenase (TDO2) were associated with inflammatory processes (Orabona et al, 2008). TDO2 could trigger the proliferation and migration of fibroblasts and result in joint destruction (Rong et al, 2022). A major metabolite, 5‐hydroxytryptamine (5‐HT), had been shown to activate multiple immune cells when combined with 5‐HT receptors (5‐HTRs), and a deficiency of 5‐HT has been related to the formation and activation of osteoclasts in RA (Chabbi‐Achengli et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…TDO2 could trigger the proliferation and migration of fibroblasts and result in joint destruction (Rong et al, 2022). A major metabolite, 5-hydroxytryptamine (5-HT), had been shown to activate multiple immune cells when combined with 5-HT receptors (5-HTRs), and a deficiency of 5-HT has been related to the formation and activation of osteoclasts in RA (Chabbi-Achengli et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, in other diseases, such as hepatocellular carcinoma, it has been found that TDO2 expression contributes to the secretion of interleukin-6 (IL-6), which promotes tumour cell proliferation through STAT3 and NF-kB/TIM4 signalling [29]. In osteoarthritis patients, TDO2 levels were signi cantly and positively correlated with IL-1β and TNF-α levels, suggesting that high levels of TDO2 in the synovium may correlate with pro-in ammatory cytokines and the severity of osteoarthritis [30]. Among these, IL-6 plays a vital role in the in ammatory process, and studies have found higher levels of IL-6 in DM patients than in healthy populations [31].…”
Section: Discussionmentioning
confidence: 99%